Effect of CdS and In3Se4 BSF layers on the photovoltaic performance of PEDOT:PSS/n-Si solar cells: Simulation based on experimental data - Mondal, Bipanko Kumar; Mostaque, Shaikh Khaled; Rashid, Md. Abdur; Kuddus, Abdul; Shirai, Hajime; Hossain, Jaker (Superlattices and microstructures, 2021)
In this article, we perform a theoretical analysis on PEDOT:PSS/n-Si heterojunction solar cells for further enhancement of the solar cells. We introduced CdS and In3Se4 chalcogenide compounds as back surface field (BSF) layer in the solar cell. The impacts of various parameters such as the thickness, doping and defect densities on the photovoltaic performance have been investigated in details employing the solar cell capacitance simulator (SCAPS-1D) software. It is found that the power conversion efficiency (PCE) of the PEDOT:PSS/n-Si heterojunction solar cells significantly increases with use of these BSF layers. The optimized PCE of the PEDOT:PSS/n-Si solar cell is 22.46% which increases to 30.94% with VOC = 0.89 V, JSC = 44.02 mA/cm2 and FF = 78.92%, respectively due to the use of CdS BSF layer. On the other hand, the PCE of the solar cell is found to be 38% with VOC = 0.84 V, JSC = 53.22 mA/cm2 and FF = 85.11%, respectively as a result of longer wavelength absorption in In3Se4 BSF layer. These entire theoretical predictions indicate the promising applications of CdS and In3Se4 compounds as BSF layers in PEDOT:PSS/n-Si heterojunction solar cells to harness solar energy in near future. [Display omitted] •Design guideline to fabricate high-efficiency PEDOT:PSS/n-Si solar cells using CdS and In3Se4 BSF layers.•The simulation reveals that CdS and In3Se4 BSF layers have significant effects on the performance of the solar cells.•The optimized PCE of the PEDOT:PSS/n-Si solar cell is 22.46% which increases to 30.94% with use of CdS BSF layer.•The PCE of the PEDOT:PSS/n-Si solar cell further increases to 38% with use of In3Se4 BSF layer.